The use of the new base gel in Hospital Recipe’s practice. - Witold Stefan Jucha; Barbara Pandyra - Kowalska (Farmacja Polska, 2020)
Semi-solid preparations for application to skin - including ointments - are one of the most commonly prescribed by doctors as well as made in pharmacies nowadays. Due to the registration of new raw materials (for compounding) in the form of gels in the Polish market, new possibilities are opening up for the preparation of prescription drugs while gels formulations have been widely used in Europe for some time. The gel form is defined in the Polish Pharmacopoeia XI as the substrate consisting of gel liquids with appropriate gelling substances. The gels have been divided into lipophilic (oleogels) and hydrophilic gels (hydrogels). A thriving compounding section of the pharmacy in the University Hospital in Krakow is an excellent intellectual and technological base of the production of new formulations of prescription drugs. They have already gained extensive experience working in the preparation of drugs based on new gel substrate (Celugel, Oleogel) as preparations for external and internal use have been made there. The characteristics of a hydrogel-like substrate: composition (water, HEC, glycerol, preservatives); the characteristics of its properties: form, consistency, possibility of combining with ethanol, intended use depending on the skin type and there is also possibility and conditions of sterilization. The characteristics of an oleogel substrate: composition (liquid paraffin, polyethylene); characteristics of its properties: form, consistency, intended use depending on the skin type. There are numerous examples of various prescription compositions that are produced in the hospital pharmacy, also during in the era of coronavirus when the need for systematic hand disinfection and wearing gloves gave rise to a number of skin problems: examples and methods of preparing prescription compositions using Celugel for the skin such as disinfecting-protective gel, anti-itch gel, acne gel, demodicosis gels with antibiotics and many others; examples of ENT and dental preparations; examples of prescription compositions using Oleogel such as bedsores care preparations, vitamin gels, preparations for psoriasis and others.